Design of foundations accounting for parametric uncertainties and comparison with Eurocode 7 - Tan, Qiuhan (2019)
Eurocode has become the main standards for structural design of buildings and civil engineering works in Singapore. Even though it is one of the world's most advanced and established building codes, it has its own limitation. It is very conservative and do not produce much insights to the relationships between the parameters. Two methods of analysis and design using First-order reliability method (FORM) were proposed by Low and Tang in 2004 and 2007, which can complement with the Eurocode. This report will compare designing using partial factor method and reliability-based design. A case study will be used and analysed in different settings to discuss the pros and cons of the partial factor method and RBD.